The Stability of the Elderly in Cross-Generational Families - Dechakhamphu, Kotchakorn (Local Administration Journal, 2023)
This research article aims to 1) studies the level of stability of the elderly in cross-generational families and 2) compares the stability of the elderly in cross-generational families. This research was a quantitative research. The study sample consisted of 420 elderly people in cross-generational families. The sample size was calculated using the Taro Yamane formula. The tool used to collect the data was the estimation scale questionnaire. The confidence value for the was 0.80. The statistics used in the analysis were percentage, mean and standard deviation, t-test, and F-test statistics. The results found that 1) the overall level of stability among the elderly in cross-generational families was at a high level. The aspect with the highest average was family, followed by housing and environment and safety of life and property. The two moderate-level aspects were health and economic and social aspects respectively. 2) The comparison of the stability of the elderly in cross-generational families found that the elderly with different ages, educational levels, marital status, family characteristics, and savings had overall life stability had a statistically significant difference at the 0.05 level.